Ruthenium–NHC‐Catalyzed Asymmetric Hydrogenation of Flavones and Chromones: General Access to Enantiomerically Enriched Flavanones, Flavanols, Chromanones, and Chromanols1. Issue 32 (1st July 2013) - Zhao, Dongbing; Beiring, Bernhard; Glorius, Frank
<x xml:space="preserve">Abstract</x> Two to four! Readily available flavones and chromones were efficiently converted into four valuable chiral classes of O‐heterocycles—flavanones, chromanones, flavanols, and chromanols—by means of an enantioselective Ru/NHC‐catalyzed hydrogenation process (see scheme; NHC=N‐heterocyclic carbene, PCC=pyridinium chlorochromate).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>